Assessment of climate change impact on major crops of the southern agroclimatic zone of Tamil Nadu, India - RAMACHANDRAN A.; PAVITHRAPRIYA S.; AHAMED IBRAHIM S N; PRAVEENKUMAR P.; MATHAN M.; KURIAN JOSEPH (Journal of Agrometeorology)
Climate change poses significant risks to crop production, endangering food security and farmer livelihoods. The southern agro-climatic zone of Tamil Nadu is particularly susceptible to droughts and floods. This study assessed the future impacts of climate change on crop yields using the DSSAT crop simulation model, with climate projections based on the EC-Earth statistical downscaled model under the SSP2-4.5 scenario for the baseline period (1985–2014) and near-century projections (2021–2050). Projections indicate a rise in annual mean maximum temperature of 0.4°C and a 7% increase in rainfall. Simulated yields of rice, maize, sorghum, and groundnut are expected to decline by 5.6%, 2.1%, 8.2%, and 7.6%, respectively, due primarily to heat stress during critical reproductive stages and altered rainfall distribution affecting crop water availability. In contrast, black gram yield is projected to increase by 4.8%, benefiting from enhanced CO2 fertilization and improved rainfall during its growing season. The study highlights the significant effects of climate change on agricultural productivity and the urgent need for adaptation strategies, including drought-resistant crop varieties, modified planting calendars, and enhanced water management techniques to build regional agricultural resilience in Tamil Nadu.